Deciphering the nonsense-mediated mRNA decay pathway to identify cancer cell vulnerabilities for effective cancer therapy - Roberta Bongiorno (BMC, 2021)
Abstract Nonsense-mediated mRNA decay (NMD) is a highly conserved cellular surveillance mechanism, commonly studied for its role in mRNA quality control because of its capacity of degrading mutated mRNAs that would produce truncated proteins. However, recent studies have proven that NMD hides more complex tasks involved in a plethora of cellular activities. Indeed, it can control the stability of mutated as well as non-mutated transcripts, tuning transcriptome regulation. NMD not only displays a pivotal role in cell physiology but also in a number of genetic diseases. In cancer, the activity of this pathway is extremely complex and it is endowed with both pro-tumor and tumor suppressor functions, likely depending on the genetic context and tumor microenvironment. NMD inhibition has been tested in pre-clinical studies showing favored production of neoantigens by cancer cells, which can stimulate the triggering of an anti-tumor immune response. At the same time, NMD inhibition could result in a pro-tumor effect, increasing cancer cell adaptation to stress. Since several NMD inhibitors are already available in the clinic to treat genetic diseases, these compounds could be redirected to treat cancer patients, pending the comprehension of these variegated NMD regulation mechanisms. Ideally, an effective strategy should exploit the anti-tumor advantages of NMD inhibition and simultaneously preserve its intrinsic tumor suppressor functions. The targeting of NMD could provide a new therapeutic opportunity, increasing the immunogenicity of tumors and potentially boosting the efficacy of the immunotherapy agents now available for cancer treatment.